SOCIAL CONSTRUCTION OF GREEN REVOLUTION IN THE ORDE BARU - Nugroho, Wahyu Budi (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol.12, No.1, 2018, 2018)
This paper seeks to examine the application and implications of the Green Revolution in the country through the perspective of social construction Mary E. Pettenger. In her analysis, the perspective of Pettenger's social construction involves the dimensions of power, knowledge, social norms, and discourse or discourse. In Indonesia, the Green Revolution is better known as "Panca Usaha Tani" which is sensitive to the modernization or mechanization of agriculture. Through the studies that have been carried out, it is clear if the “Orde Baru” regime uses resources of power, knowledge, social norms, and discourse in an effort to promote the mechanization of agriculture in the country. A series of dimensions are arranged into a form of social construction that successfully hides various hidden interests in it, among others; national socio-political stability, the legitimacy of debts on the part of the parties, alignments with the West Bloc, and efforts to make Indonesia a rice barn for developed countries.